Zircon U–Pb Ages and Geochemistry of Granitoid in the Yuejinshan Copper–Gold Deposit, NE China: Constraints on Petrogenesis and Metallogenesis - Qingshuang Wang (MDPI AG, 2021)
Yuejinshan copper–gold orebodies form a hydrothermal deposit located southwest of the Wandashan massif in the western Pacific oceanic tectonic regime. The orebodies are veins and lenses in granite porphyry and skarn or contact zones between these rocks. Early Cretaceous Yuejinshan magmatism provides critical evidence for regional mineralization and tectonic history. In this work, whole-rock major and trace elements and zircon U–Pb data for Yuejinshan granitic intrusions were studied to investigate the geochronological framework, petrogenesis, tectonic implications, and metallogenesis. Granodiorites are calc-alkaline and have geochemical characteristics that indicate affinities with subduction-related crust–mantle magmas derived from partial melting of a mantle wedge and subducted sediments metasomatized by subduction-related fluids. These magmas have experienced fractional crystallization and assimilated crustal materials. Granite porphyries, monzogranites, and quartz diorites are peraluminous, geochemically similar to remelted granites, and derived from partial melting of the crust. Zircon U–Pb LA-ICP-MS data and previous ages indicate that the granitoids were emplaced in the Early Cretaceous. We propose that mineralization mainly occurred at 130 Ma, while magmatism during 116–109 Ma triggered the enrichment of copper and gold in this deposit. Magmatism of different geological ages overlapped spatially and formed the Yuejinshan copper–gold deposit in an active continental margin setting related to the subduction of the Paleo-Pacific Plate.